PRINCIPALS’ SCHOOL PLANT MAINTENANCE STRATEGIES, AS DETERMINANT OF QUALITY ASSURANCE IN PUBLIC SECONDARY SCHOOLS IN ENUGU STATE - Uche , Boniface Nnamdi; Ezeilo, Nkechi Hope (Journal of Continuing and Development Education, 2024)
This study was carried out to examine principals’ School Plant Maintenance strategies as Determinant of Quality Assurance in Public secondary schools in Enugu State. The design adopted for the study was descriptive survey research Design. The population comprised of 298 principals and 826 Teachers in the 298 public secondary schools in the state. A researcher-developed instrument titled “Principals School Plant Maintenance Strategies Questionnaire” (PSPMSQ) was used for data collection. PSPMSQ was duly validated. The co-efficient of .79 was obtained for PSPMSQ using Cronbach Alpha method. The researcher collected the data from the respondents. The research question was answered using mean and standard deviation while t-test was used to test the hypotheses at .05 level of significance. Findings indicated that respondents agreed on principals’ strategic planning and organizing of school plant maintenance in secondary schools will to a great extent determine the achievement of quality assurance in Public Schools.